2014
DOI: 10.4018/joeuc.2014100102
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Cyberloafing through a Theoretical Integration of Theory of Interpersonal Behavior and Theory of Organizational Justice

Abstract: Cyberloafing is an issue of growing concern for contemporary organizations. This paper develops an integrated research model which combines the Theory of Interpersonal Behavior and Organizational Justice to provide a holistic examination for cyberloafing behavior. Data was collected from working respondents via on-line questionnaire to test the research model. The results of this study found that the metaphor of the ledger from the organizational justice model was a significant predictor of intent to cyberloaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Extant findings suggest some form of normative information is driving cyberloafing. First, social norms are a consistent predictor of cyberloafing and have shown strong relationships with cyberloafing across diverse work environments (Betts et al, 2014; Bock et al, 2010; Freimark, 2012; Galluch & Thatcher, 2007; Liberman et al, 2011; Polzer-Debruyne et al, 2014; Sheikh et al, 2015; Taneja, 2006). Moreover, most of these observed associations have been medium to large in magnitude (Cohen, 1988).…”
Section: Social Norms and Cyberloafingmentioning
confidence: 99%
See 3 more Smart Citations
“…Extant findings suggest some form of normative information is driving cyberloafing. First, social norms are a consistent predictor of cyberloafing and have shown strong relationships with cyberloafing across diverse work environments (Betts et al, 2014; Bock et al, 2010; Freimark, 2012; Galluch & Thatcher, 2007; Liberman et al, 2011; Polzer-Debruyne et al, 2014; Sheikh et al, 2015; Taneja, 2006). Moreover, most of these observed associations have been medium to large in magnitude (Cohen, 1988).…”
Section: Social Norms and Cyberloafingmentioning
confidence: 99%
“…Moreover, most of these observed associations have been medium to large in magnitude (Cohen, 1988). Second, social norm variables have shown incremental validity over other established predictors of cyberloafing, such as attitudes toward cyberloafing (Liberman et al, 2011), electronic monitoring (Taneja, 2006), self-efficacy to hide cyberloafing (Sheikh et al, 2015), and organizational justice (Betts et al, 2014). Thus, it is likely the observed association between social norms and cyberloafing cannot be explained by other established predictors.…”
Section: Social Norms and Cyberloafingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Theory of Interpersonal Behaviour ([TIB], Triandis, 1977), while similar to the TPB, includes the influence of habit and posits that it is inversely related to intention (Triandis, 1977). Research has applied the TIB to personal internet use in the workplace where habit was found to be significantly and positively related to behaviour (Betts, Setterstrom, Pearson, & Totty, 2014;Moody & Siponen, 2013).…”
Section: Theoretical Considerationsmentioning
confidence: 99%